Principles of economics with taxation and agrarian reform : a modular approach - Azarcon, Ernie Roy S.; Marzo, Rosario M.; Navarro, Gladys M.; Degay-Paragas ; Degay-Paragas, Imelda ; Sison-Paragas, Nicetas ; Rojo, Elaine Geraldine E. (Baguio City, 2008)
Principles of Economics with Taxation and Agrarian Reform ( A modular approach) 2nd edition is a book that has been a product of many years of tecahing the course. The authors of this book, all professors of Saint Louis university, were challenged to make the course far more appealing and hopefully a lot easier for all basic economics students. This work is a humble attempt to simplify the course using a modular structure, yet present it in an interesting and interactive manner
Keywords: Economics